Geographic Distribution of Vaccinia Virus, Diagnosis and Demographic Aspects of Affected Populations, Minas Gerais, Brazil, 2000–2023 - Pedro H. B. e Silva; Maycon D. de Oliveira; Iara M. de Almeida; Iago J. S. Domingos; Ana G. Stoffella-Dutra; Galileu Barbosa Costa; Jaqueline S. de Oliveira; Felipe C. M. Iani; Márcio R. de Castro; Jonatas S. Abrahão; Erna G. Kroon; Giliane de S. Trindade (Viruses)
Since its first report in Brazil in 1999, outbreaks of exanthematous diseases caused by vaccinia virus (VACV) have been a recurring concern, particularly impacting rural regions. Minas Gerais (MG) State, Brazil, has emerged as the epicenter of bovine vaccinia (BV) outbreaks. This study presents a comprehensive overview of VACV circulation in MG State over the past two decades, examining the occurrence and distribution of poxvirus cases and outbreaks and the demographic characteristics of affected populations. Analysis of secondary databases from 2000 to 2023 revealed VACV circulation in at least 149 municipalities, particularly expanding in dairy regions. The study underscores BV as an occupational disease, predominantly affecting rural men involved in dairy cattle activities. Laboratory findings indicate high levels of anti-OPXV antibodies in most individuals, with some showing acute infections confirmed by qPCR testing. This analysis informs public health policies, emphasizing the need for enhanced surveillance of and preventive measures for dairy farming communities.